Primary B-cell non-Hodgkin lymphoma of the larynx in children: report of two cases and a review of the literature - Coşkun, Çağrı; Kurucu, Nilgün; Kutluk, Tezer; Yılmaz, Taner; Bulut, Elif; Üner, Ayşegül (The Turkish Journal of Pediatrics, 2025)
Background. Non-Hodgkin lymphoma of the larynx in children is a rare condition. Diagnosis is difficult as its symptoms are usually attributed to respiratory tract infections and pubertal voice changes.Case Presentations. We report two children diagnosed with laryngeal B-cell lymphoma based on imaging and histopathological findings. We also review other pediatric cases of laryngeal lymphoma documented in the literature, detailing tumor locations, lymphoma types, stages, etiological factors, and treatment regimens of these patients.Conclusion. Diagnosis of laryngeal lymphoma is challenging. Although certain imaging features can be suggestive of the disease, a definitive diagnosis requires histopathological examination. Surgery is not required for the treatment, and chemotherapy is the main treatment approach. Early diagnosis is important.
Keywords: laryngeal lymphoma; non-Hodgkin lymphoma; children